Building Environmental Management Accounting in Shipping Industry - Maulita Maulita; Ari Wibowo; Herdi Syam (Cita Konsultindo Research Center, 2023)
Sustainable development is an international issue of concern to the industry, including the shipping industry. The dense activity of the shipping industry makes the shipping industry one of the contributors to environmental pollution. Therefore, environmental accountability is one of the important aspects of corporate social responsibility to reduce the environmental damage caused by company activities. Environmental Management Accounting can improve environmental sustainability by evaluating information related to finance and the physical environment in the shipping industry. Coersive pressure, Green Shipping and Regulatory Pressure of the shipping industry are variables that in this study are considered to influence the adoption of Environmental Management Accounting. 120 questionnaires are distributed via WhatsApp, and as many as 100 questionnaires can be processed. The research data was analysed using Smart PLS. This study found that Coersive Pressure did not significantly affect EMA adoption in the shipping industry. In contrast, Green Shipping and Regulatory Pressure positively and significantly affected EMA adoption in the Shipping industry. The study concluded that Green Shipping and regulatory Pressure positively and significantly affected EMA adoption in the shipping Industry. In contrast, Coersive Pressure did not positively and significantly affect EMA Adoption.